Binary Soft Connected Spaces and an Application of Binary Soft Sets in Decision Making Problem - Hussain, Sabir (Fuzzy information and engineering, 2019)
One of the most important and basic topological properties is connectedness, which reflects the main characteristic of topological spaces and helps us to differentiate two topologies. Keeping in mind the importance of this concept, we initiate binary soft connectedness in binary soft topological spaces and explore its properties. It is interesting to mention that union of two binary soft connected spaces over and may not be a binary soft connected space. We also define and discuss binary soft boundary in binary soft topological spaces and establish the characterisation of binary soft connected spaces in terms of binary soft boundary. Moreover, we present an application of binary soft sets theory in decision making problem. We expect that this will be potentially useful research in theoretical as well as in any applicable directions to handle the problems of uncertainties and environment having ambiguities.